PEMBERDAYAAN KADER DALAM DETEKSI DINI DAN KONSELING BALITA STUNTING DI WILAYAH PUSKESMAS BERINGIN RAYA KOTA BENGKULU TAHUN 2023 - Maigoda, Tonny; Rizal, Ahmad; Natan, Okdi (Poltekkes Kemenkes Bandung, 2024)
The aim of this community engagement is to empower health/posyandu cadres in detecting early child growth and development and providing nutritional counseling to mothers who have stunted toddlers. The activity methods used in this activity were lectures, discussions, questions and answers to cadres, counseling to mothers of stunted toddlers, and early detection practice training for cadres for a total of 3 days of activities. The results of the socialization activities showed that there was an increase in knowledge before the socialization obtained an average value of 32.38 with a standard deviation of 6.637 and after obtaining a value of 80.71 with a standard deviation of 5.542. There was a change in knowledge before and after the socialization of cadre knowledge before and after training in the Beringin Raya Community Health Center area with a P-value of 0.001. In Conclusion, there is a gain of knowledge before and after socialization, an increase in practicing cadres' ability to do of anthropometric measurements, and the ability to early detect of stunting in the Beringin Raya Bengkulu Community Health Center Area.